Low-characteristic-impedance superconducting tadpole resonators in the sub-gigahertz regime - Miika Rasola; Samuel Klaver; Jian Ma; Priyank Singh; Tuomas Uusnäkki; Heikki Suominen; Mikko Möttönen (Physical Review Research, 2024)
We demonstrate a simple and versatile resonator design based on a short strip of a typical coplanar waveguide shorted at one end to the ground and shunted at the other end with a large parallel-plate capacitor. Due to the shape of the structure, we coin it the tadpole resonator. The design allows tailoring the characteristic impedance of the resonator to especially suit applications requiring low values. We demonstrate characteristic impedances ranging from Z_{c}=2 to 10Ω and a frequency range from f_{r}=290MHz to 1.1GHz while reaching internal quality factors of order Q_{int}=8.5×10^{3} translating into a loss tangent of tan(δ)=1.2×10^{−4} for the aluminum oxide used as the dielectric in the parallel-plate capacitor. We conclude that these tadpole resonators are well suited for applications requiring low frequency and low characteristic impedance while maintaining a small footprint on chip. The low characteristic impedance of the tadpole resonator renders it a promising candidate for achieving strong inductive coupling to other microwave components.